Labour relations within the BRICS: common core and prospects of supranational regulations - BELIKOVA, K. M (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The impact of globalization leads to increasing flows of cross-border labor mobility. The goal of the current study is the development of the world economy. The methodology used consist of reviewing and analyzing legal approaches of BRICS countries in the field under study. The obtained results indicated that the approach of the applicability or non-application of the rules of international law within the BRICS actually affects the scope of international private law. RESUMEN Es obvio que el impacto de la globalización conduce a flujos crecientes de movilidad laboral transfronteriza. El objetivo del presente estudio es el desarrollo de la economía mundial. Las metodologías que se han utilizado consisten en revisar y analizar los enfoques legales de los países BRICS en el campo en estudio. Los resultados obtenidos indicaron que el enfoque de los estados nacionales para la aplicación o no aplicación de las normas de derecho internacional dentro de los BRICS en realidad afecta el alcance del derecho privado internacional.